PEMERIKSAAN KEHADIRAN LOGAM DAN KADAR TERCEMARNYA AIR BAKU SEBAGAI DAMPAK PENGGUNAAN WC APUNG KOTA BANJARMASIN - Saptarini, Dessy Lestari; Rizani, Ahmad; Salmani (Politeknik Negeri Banjarmasin, 2024)
Water quality that meets environmental quality standards is very necessary for living creatures. Water quality is generally expressed by parameters such as physics, chemistry and biology. It is important to know the quality of river water because river water is the main need of the people of Banjarmasin city, the majority of whom live along the banks of the Martapura River. Community service activities are carried out in the Banjarmasin city area with the collaboration partner being the 9 November Banjarmasin Community Health Center. The team from the 9 November Community Health Center has innovated a river septic tank called the S Plus Subarwakat septitank. This septic tank innovation is applied to public places located on the edge of or above rivers. Therefore, the service team from Poliban will measure the quality of river water using this septic tank innovation. The method for measuring river water quality uses a multiparameter tool which produces water quality parameters such as TDS levels or dissolved solids, oxygen content, acidity or pH levels, salinity levels, etc